2018
DOI: 10.5603/gp.a2018.0064
|View full text |Cite
|
Sign up to set email alerts
|

The value of serum uric acid in predicting adverse pregnancy outcomes of women with hypertensive disorders of pregnancy

Abstract: Women with HDP and HUA are often accompanied with a variety of abnormal biochemical indicators, and is correlated with the severity of the disease and APOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The odds ratio of adverse pregnancy outcomes with serum uric acid levels >357μmol/L was 1.258, p<0.05. 11 This is similar to the findings of the current study, as stated above. Two other studies reported similar findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The odds ratio of adverse pregnancy outcomes with serum uric acid levels >357μmol/L was 1.258, p<0.05. 11 This is similar to the findings of the current study, as stated above. Two other studies reported similar findings.…”
Section: Discussionsupporting
confidence: 92%
“…The sample size was calculated using Net's sample size calculator taking 6% Population Proportion. 11 The subjects were enrolled through nonprobability, consecutive technique.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Lin et al from 2015 to 2017, 180 pregnant women with hypertensive disease of pregnancy were put into two sub Group-s based on their uric acid levels. 13 One Group-had raised maternal serum uric acid (n=137), and the other had normal levels (n=43). The pregnancy outcomes were compared with another Group of 180 healthy pregnant women.…”
Section: Discussionmentioning
confidence: 96%
“…4 One study found that frequency of low birth weight was 36.2% in women having hyperuricemia & hypertension during pregnancy. 5 Study carried by Ryu et al mean uric acid level was 5.8 ranging from (4.7 -6.6) in pre-eclamptic women compared to 3.9 and ranging from (3.1 -4.6) in patients with normal blood pressure. Pre-eclampsia was associated significantly with preterm labor, LBW (low birth weight) and SGA (small for Gestational age).…”
Section: Introductionmentioning
confidence: 94%